Four-week omega-3 polyunsaturated fatty acids supplementation for liver left lateral section volume reduction in individuals with morbid obesity undergoing bariatric surgery: A double blind, multicenter, randomized placebo-controlled trial. (May 2022) - Iannelli, Antonio; Fontas, Eric; Grec, Laurence; Nocca, David; Robert, Maud; Schiavo, Luigi; Schneck, Anne-Sophie
Abstract: Background: Liver steatosis in morbidly obese individuals undergoing bariatric surgery increases liver volume and may complicate the surgical procedure. This study aimed to assess whether a 4-week supplementation with omega-3 polyunsaturated fatty acids (PUFA) is effective in reducing liver left lateral section (LLLS) volume. Patients and methods: This randomized controlled trial included morbidly obese individuals with metabolic syndrome undergoing bariatric surgery at 3 French bariatric centers between 2017 and 2020. The experimental group had a 4-week preoperative supplementation with omega-3 PUFA, whereas the control group had only placebo. The primary outcome was the reduction of the LLLS volume measured with Magnetic Resonance Imaging (MRI). Results: 42 patients were randomized and 37 completed the study (19 in the experimental group and 18 in the placebo group). The mean LLLS volume decreased of 3.3% (±9.6) in the experimental group vs 1.0% (±18.3) in the placebo group, indicating that omega-3 PUFA were not effective in reducing the LLLS volume compared to the placebo (p = 0.3741). Omega-3 PUFA supplementation was not effective in reducing total liver volume, liver steatosis, rate of liver injuries during surgery and operative time. Conclusion: A 4-week preoperative supplementation with omega-3 PUFA was not effective in reducing LLLS volume in morbidly obese individuals undergoing bariatric surgery. Highlights: Preoperative Omega-3 polyunsaturated fatty acids (PUFA) are not effective to reduce liver volume. Bariatric surgery prepared by Omega 3 PUFA is not associated with better outcome. Other strategies should be privileged to improve bariatric surgery outcomes.